Pengaruh Customer Experience, Service Quality Dan Perceived Value Pada Pengguna Premium Terhadap Loyalitas Pelanggan Streaming Spotify - Putri, Weni Anita; Maslichah, Maslichah; Efendi, Erfan (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the effect of customer experience, service quality, and perceived value on customer loyalty in users of Spotify premium streaming services. Data collection was carried out using a purposive sampling method on 85 respondents who had used Spotify premium services, through a Likert Scale-based questionnaire. Data analysis was carried out by multiple linear regression and hypothesis testing (F test and t test) using the IBM SPSS version 20 program. The results showed that simultaneously, the three variables had a positive and significant effect on customer loyalty (significance 0.000 <0.05). Partially, customer experience, service quality, and perceived value also have a significant effect on customer loyalty. Keywords: Customer Experience, Service Quality, Perceived Value and Customer Loyalty.